PENGARUH FINANCIAL STABILITY, PERSONAL FINANCIAL NEED, INEFFECTIVE MONITORING, CHANGE IN AUDITOR DAN CHANGE IN DIRECTOR TERHADAP FINANCIAL STATEMENT FRAUD DALAM PERSPEKTIF FRAUD DIAMOND (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efe - Regina Aprilia; Hardi '; Al-Azhar A ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to obtain empirical evidence about the effectiveness of the fraud diamond in detecting financial statement fraud. The element of the fraud diamond that is used as independent variables is a pressure with proxy financial stability (ACHANGE) and personal financial need (OSHIP), opportunity with proxy ineffective monitoring (BDOUT), rationalization with proxy change in auditor (AUDCHANGE), and capability with proxy change in director (DCHANGE). In this research uses a proxy earnings management with discretionary accruals as the dependent variable. The population of this research is the manufacturing companies listed in Indonesia Stock Exchange in 2012-2014. Total sample of this research is 89 manufacturing companies. Data analysis was performed with the classical assumption and hypothesis testing using multiple linear regression. The results indicates that the financial stability (ACHANGE) and ineffective monitoring (BDOUT) influence the financial statement fraud. Meanwhile, the personal financial need (OSHIP), change in auditor (AUDCHANGE), and change in director (DCHANGE) has no significant impact on financial statement fraud.The influence of the independent variables to describe the dependent variable is 21,8%, while the remaining 78,2% is influenced by other variables.Keywords: Financial Statement Fraud, Earnings Management, Fraud Diamond.